1989
DOI: 10.3168/jds.s0022-0302(89)79300-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rumen-Mate® on Lactational Performance of Holsteins Fed a High Grain Diet

Abstract: Three Latin-square trials were conducted to determine the effects of supplementing Rumen-Mate, a commercial buffer containing KCl, NaCl, and Mg and Na carbonates, on lactation performance of Holsteins. Cows were fed a basal ration of 40% corn silage and 60% concentrate in Trials 1 and 2, and 40% corn silage, 55% concentrate, and 5% alfalfa hay in Trial 3 (DM basis). In Trial 1, treatments were: basal diet, or basal diet supplemented with either 1% NaHCO3, or 1, 3, or 4.4% Rumen-Mate. Increasing dietary Rumen-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…With the aim of controlling rumen pH, many studies have evaluated the use of supplementing rations with buffers or alkalinizers (or neutralizing agents) such as sodium bicarbonate or magnesium oxide, respectively, as well as supplementing live yeast (Thrune et al, 2009;DeVries and Chevaux, 2014) and yeast cultures (Poppy et al, 2012). Most studies have reported increases in DMI (Erdman et al, 1982;Rogers et al, 1985a;Staples et al, 1988), milk yield (Kilmer et al, 1981;Thomas et al, 1984;Rogers et al, 1985a), and milk fat content (Rogers et al, 1985a;Solorzano et al, 1989) when cows were supplemented with sodium bicarbonate, although some (Donker and Marx, 1980;DePeters et al, 1984;Rogers et al, 1985b) found no responses. Whether changes were directly caused by sodium bicarbonate or by an increase in DCAD is unknown, but several authors have reported improvements in milk yield and DMI when DCAD is increased (Sanchez and Beede, 1996;Hu and Murphy, 2004;Iwaniuk and Erdman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of controlling rumen pH, many studies have evaluated the use of supplementing rations with buffers or alkalinizers (or neutralizing agents) such as sodium bicarbonate or magnesium oxide, respectively, as well as supplementing live yeast (Thrune et al, 2009;DeVries and Chevaux, 2014) and yeast cultures (Poppy et al, 2012). Most studies have reported increases in DMI (Erdman et al, 1982;Rogers et al, 1985a;Staples et al, 1988), milk yield (Kilmer et al, 1981;Thomas et al, 1984;Rogers et al, 1985a), and milk fat content (Rogers et al, 1985a;Solorzano et al, 1989) when cows were supplemented with sodium bicarbonate, although some (Donker and Marx, 1980;DePeters et al, 1984;Rogers et al, 1985b) found no responses. Whether changes were directly caused by sodium bicarbonate or by an increase in DCAD is unknown, but several authors have reported improvements in milk yield and DMI when DCAD is increased (Sanchez and Beede, 1996;Hu and Murphy, 2004;Iwaniuk and Erdman, 2015).…”
Section: Introductionmentioning
confidence: 99%